Comparison of Mean Platelet Volume in Patients with and Without Diabetes Mellitus at a Tertiary Care Hospital - Ashraf, Jahanzaib; Farrukh, Uffaq; Bhalli, Amanullah; Syed, Uneeba (Biological and Clinical Sciences Research Journal, 2025)
Mean Platelet Volume (MPV) is a platelet activation marker linked to various cardiovascular diseases. Type 2 Diabetes Mellitus (T2DM) is known to increase the risk of thrombosis, and changes in platelet characteristics, including MPV, may contribute to this risk. Objective: This study aimed to compare the MPV in patients with and without T2DM at a tertiary care hospital. Methods: This randomized controlled trial was conducted at Akhtar Saeed Trust Hospital, Lahore, with 98 participants (49 diabetic and 49 non-diabetic) from 18 October 2024 Till 17 January 2025. Data were collected through non-probability consecutive sampling. MPV, fasting blood glucose (FBG), and HbA1c were measured for each patient. Results: The mean MPV was significantly higher in the diabetic group (9.94 ± 1.07 fL) compared to the non-diabetic group (9.36 ± 0.96 fL), with a p-value of 0.001. FBG and HbA1c levels were also significantly higher in the diabetic group. Stratified analysis showed consistent results across age and BMI categories, confirming that these factors did not confound the difference in MPV. Conclusion: It is concluded that T2DM is associated with higher MPV, suggesting increased platelet activation in diabetic patients. This may contribute to the elevated cardiovascular risk observed in this population. MPV could potentially serve as a biomarker for platelet dysfunction in diabetes, but further research is needed to explore its clinical significance and predictive value.